The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1103/physrevx.10.041019
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Smooth Polaron-Molecule Transition in a Degenerate Fermi Gas

Abstract: Understanding the behavior of an impurity strongly interacting with a Fermi sea is a long-standing challenge in many-body physics. When the interactions are short ranged, two vastly different ground states exist: a polaron quasiparticle and a molecule dressed by the majority atoms. In the single-impurity limit, it is predicted that at a critical interaction strength, a first-order transition occurs between these two states. Experiments, however, are always conducted in the finite temperature and impurity densi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 104 publications
(183 reference statements)
4
105
0
Order By: Relevance
“…We restrict ourselves here to the case of immobile impurities. The case of mobile impurities has been extensively studied for fermionic systems both theoretically [30][31][32][33][34][35][36] and experimentally [37]. The set up of immobile impurities that we study in this paper is more difficult to access experimentally, however it has been suggested that impurities could be introduced by superimposing an optical lattice on an overall trapping potential [38].…”
Section: Introductionmentioning
confidence: 99%
“…We restrict ourselves here to the case of immobile impurities. The case of mobile impurities has been extensively studied for fermionic systems both theoretically [30][31][32][33][34][35][36] and experimentally [37]. The set up of immobile impurities that we study in this paper is more difficult to access experimentally, however it has been suggested that impurities could be introduced by superimposing an optical lattice on an overall trapping potential [38].…”
Section: Introductionmentioning
confidence: 99%
“…Finite temperature effect may favor the stabilization of the system against collapse [57]. In addition, both a non-negligible concentration of impurities and finite temperature effects may combine, changing the polaron properties drastically in comparison with the single impurity case at T = 0, as recently revealed for Fermi polarons [58]. Finally, another avenue is studying the role of the direct impurity-impurity interaction and its influence on forming a gas or liquid of polarons and the role of bosonic quasi-particles in the formation of self-bound structures [59][60][61].…”
Section: Discussionmentioning
confidence: 87%
“…In the present polaron context, this measurement would have to be performed in a state-dependent manner to extract the Hall drag. In addition, one could conduct either a state-dependent time-of-flight measurement [39,40], or Raman spectroscopy (as recently implemented for polarons [41]), to infer the in-trap momentum distribution of the impurity, in view of evaluating the current response of the impurity to an applied force.…”
Section: Measurement Of the Hall Dragmentioning
confidence: 99%